Aristotle on Accidental Causation. Issue 4 (6th February 2017) - HUISMANN, TYLER
ABSTRACT: I offer a new analysis of Aristotle's concept of an accidental cause. Using passages from Metaphysics Δ and Ε, as well as Physics II, I argue that accidental causes are causally inert. After defending this reading against some objections, I draw some conclusions about Aristotle's basic understanding of causation.